Identification of Genetic Factors Controlling the Formation of Multiple Flowers Per Node in Pepper (Capsicum spp.) - Kim, Youngin; Kim, Geon Woo; Han, Koeun; Lee, Hea-Young; Jo, Jinkwan; Kwon, Jin-Kyung; Lemmon, Zachary; Lippman, Zachary; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2022)
Flower production provides the foundation for crop yield and increased profits. Capsicum annuum is a pepper species with a sympodial shoot structure with solitary flowers. By contrast, C. chinense produces multiple flowers per node. C. annuum accounts for 80% of pepper production worldwide. The identification of C. chinense genes that control multiple flowers and their transfer into C. annuum may open the way to increasing fruit yield. In this study, we dissected the genetic factors were dissected controlling the multiple-flower-per-node trait in Capsicum. 85 recombinant inbred lines (RILs) between the contrasting C. annuum ‘TF68’ and C. chinense ‘Habanero’ accessions were phenotyped and genotyped. Quantitative Trait Loci (QTL) analysis identified four novel QTLs on chromosome 1, 2, 7, and 11 that accounted for 65% of the total phenotypic variation. Genome-wide association study was also performed on a panel of 276 genotyped and phenotyped C. annuum accessions, which revealed 28 regions significantly associated with the multiple-flower trait, of which three overlapped the identified QTLs. Five candidate genes involved in the development of the shoot and flower meristems were identified and these genes could cause multiple flowers per node in pepper. These results contribute to our understanding of multiple flower formation in Capsicum and will be useful to develop high-yielding cultivars.